2005
DOI: 10.1111/j.1439-0442.2005.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Segmental Tibial Defects Using Acute Bone Shortening Followed by Gradual Lengthening with Circular External Fixator

Abstract: The aim of this study was to clinically and radiographically evaluate acute bone shortening followed by gradual lengthening in the treatment of large segmental tibia defects induced in seven clinically normal dogs. A circular external fixator was assembled with one proximal 5/8-circle ring, one middle ring and one distal ring connected with three rods. Thirty per cent of the tibia and fibula were removed in the middle and distal parts of the diaphyses, between the middle and distal rings. Acute bone shortening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…However, postoperative complications are common, such as bone exposure and bone non- union usually along with axis deviation in long segmental bone transport, consolidation of newly formed bone is poor, delayed union or non-union can occur at the docking site, and pin track infection and screw loosening, stiffness of the knee and ankle joint foot drop can occur [5]. Many studies of the ASD technique have shown that it has obvious advantages and can significantly shorten the time of union [24,[28][29][30]. It reduces or closes the wound, effectively reduces the soft-tissue tension, and reduces the incidence of postoperative bone infection, bone exposure, osteonecrosis and soft-tissue necrosis; it is especially suitable for patients with large wounds [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postoperative complications are common, such as bone exposure and bone non- union usually along with axis deviation in long segmental bone transport, consolidation of newly formed bone is poor, delayed union or non-union can occur at the docking site, and pin track infection and screw loosening, stiffness of the knee and ankle joint foot drop can occur [5]. Many studies of the ASD technique have shown that it has obvious advantages and can significantly shorten the time of union [24,[28][29][30]. It reduces or closes the wound, effectively reduces the soft-tissue tension, and reduces the incidence of postoperative bone infection, bone exposure, osteonecrosis and soft-tissue necrosis; it is especially suitable for patients with large wounds [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…3 Comparison of external fixation index between the BT and AST groups studies. Some studies believe that docking site union is the key factor that affects the whole therapeutic time, and the AS technique is more advantageous in shortening the docking site union time [24,[28][29][30]. Therefore, the bone union time of the AS group may be shorter.…”
Section: Bone Union Timementioning
confidence: 99%
“…No statistical signi fi cances were detected in all parameters between regenerated and intact tibiae at 104 weeks. To compare (Rahal et al 2005 ) (Fig. 40.6 ).…”
Section: Dogsmentioning
confidence: 99%
“…[5] Many studies of the ASD technique have shown that it has obvious advantages and can significantly shorten the time of union. [24,[28][29][30] It reduces or closes the wound, effectively reduces the soft-tissue tension, and reduces the incidence of postoperative bone infection, bone exposure, osteonecrosis and soft-tissue necrosis; it is especially suitable for patients with large wounds. [31][32][33][34][35][36][37] However, according to two studies, [38,39] it may cause vascular and nerve injury and require more bone grafts and a limited shortening distance.…”
Section: Advantages and Disadvantages Of Ast And Bt From Previous Litmentioning
confidence: 99%
“…Some studies believe that docking site union is the key factor that affects the whole therapeutic time, and the AS technique is more advantageous in shortening the docking site union time. [24,[28][29][30] Therefore, the bone union time of the AS group may be shorter. However, bone union may be affected by many factors, such as the severity of the original injury and infection, the length of bone defect and other factors.…”
Section: Outcome Analysis Efimentioning
confidence: 99%